The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1101/lm.2.6.279
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order associative processing in Hermissenda suggests multiple sites of neuronal modulation.

Abstract: Two important features of modern accounts of associative learning are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 52 publications
5
37
2
Order By: Relevance
“…However, in discrete-trial chemosensory blocking and overshadowing experiments, we have observed opposite effects: Chemosensory stimuli potentiate conditioning to light (Farley & Jin, 1997;Farley, Reasoner, & Janssen, 1997). Nonetheless, accepting Rogers and Matzel's (1995) results at face value, we have previously discussed in detail their possible interpretation and significance (Farley et al, 1997, pp. 336-338).…”
Section: Additional Reports Of Contextual Conditioning In Hermissendamentioning
confidence: 93%
See 2 more Smart Citations
“…However, in discrete-trial chemosensory blocking and overshadowing experiments, we have observed opposite effects: Chemosensory stimuli potentiate conditioning to light (Farley & Jin, 1997;Farley, Reasoner, & Janssen, 1997). Nonetheless, accepting Rogers and Matzel's (1995) results at face value, we have previously discussed in detail their possible interpretation and significance (Farley et al, 1997, pp. 336-338).…”
Section: Additional Reports Of Contextual Conditioning In Hermissendamentioning
confidence: 93%
“…On the contrary, the animal has learned two, mutually antagonistic responses. In contrast, control animals that received nonreinforced scallop exposures during the first phase of training, followed by compound light, scallop, and rotation pairings [designated as groups (AϪ)A:P and (IOϩ/AϪ)A:P from Experiments 1 and 2 of Rogers & Matzel (1995)] showed foot contraction to light due to the unopposed light-shaking association.…”
Section: Additional Reports Of Contextual Conditioning In Hermissendamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that a chemosensory CS, when paired with rotation, suppresses bite-strike responses normally elicited by the chemosensory CS prior to conditioning (Farley et al 1990a). Rogers and Matzel (1996) reported that an excitatory context produced by presenting unsignaled USs (rotation) in a context of chemosensory stimuli blocked later conditioned foot-shortening produced by a light CS paired with rotation US within that context. More recently, it was reported that explicitly unpaired presentations of the CS and US produced conditioned inhibition expressed by increased phototactic behavior (Britton and Farley 1999).…”
Section: Pavlovian Conditioningmentioning
confidence: 99%
“…Additional evidence implicating 5-HT in the US pathway and in conditioning of Hermissenda comes from studies showing that pharmacological agents that affect 5-HT neurotransmission (imipramine, bufotenine, and 5,7-DHT) attenuate in vitro conditioning correlates in type B-photoreceptors ). In addition, 5-HT modulates generator potentials and membrane conductances in type B photoreceptors, modifications that have been identified as neural correlates of Pavlovian conditioning (Crow and Bridge 1985;Farley and Wu 1989;Acosta-Urquidi and Crow 1993;Rogers and Matzel 1995;Crow 1995, 1996). A computational model of the type B photoreceptor used to investigate the contribution of different ionic conductances modulated by 5-HT to the enhanced excitability produced by 5-HT suggested that changes in I A , I K,Ca , or I h (Yamoah et al 1998) would produce excitability changes comparable to experimental findings (Cai et al 2003).…”
Section: Convergence Of the Cs And Us Pathwaysmentioning
confidence: 99%